Transcutaneous electrical acupoint stimulation for hypertension complicated by anxiety or sleep disorders: A pilot randomized controlled trial - Xue-Ying Bao; Cun-Zhi Liu; Zi-Tong Qian; Lu Wang; Jian-Feng Tu; Bin-Yan Li; Xiao Wang; Fang Wan; Zhi-Han Li; Zhao-Yi Liu; Liang-Xiao Ma; Li-Qiong Wang (Complementary Therapies in Medicine)
Background: Hypertension is often accompanied by anxiety and sleep disorders, which further complicate the disease. This study aimed to evaluate the feasibility and effectiveness of transcutaneous electrical acupoint stimulation (TEAS) in patients with hypertension and anxiety or sleep disorders. Methods: Eligible participants were randomly assigned to the 10 Hz TEAS, 2 Hz TEAS, or routine treatment groups in a 1:1:1 ratio. Participants continued their routine treatment during the trial, while those in the two TEAS groups received 12 sessions of 30-min TEAS treatment with different stimulation frequencies. The feasibility parameters were successful screening probability, enrollment rate, and dropout rate. The primary outcome was the change in office systolic blood pressure from baseline to week four. Secondary outcomes included changes in office diastolic blood pressure, heart rate, Pittsburgh Sleep Quality Index score, and Generalized Anxiety Disorder 7-item scale score from baseline to week four. Results: Eighty-eight participants (age 58.0 [51.0, 63.0] years; 49 women) were randomized. The successful screening probability was 56.1 %, the enrollment rate was 3.1 participants per week, and the dropout rate was 14.8 %. The change in office systolic blood pressure from baseline to week four was −2.8 ± 13.6 mm Hg, −6.4 ± 10.0 mm Hg, and −7.2 ± 11.2 mm Hg, respectively, in the 10 Hz TEAS, 2 Hz TEAS, and routine treatment groups (P = 0.332). No significant differences were noted, except for a change in the Pittsburgh Sleep Quality Index score (P = 0.014). Both 10 Hz (P = 0.024) and 2 Hz TEAS (P = 0.039) significantly improved sleep quality compared to routine treatment. Conclusions: In patients with hypertension having anxiety or sleep disorders, this study did not demonstrate the superiority of TEAS over routine treatment but did show an improvement in sleep quality and a downward trend in diastolic blood pressure. Therefore, a largescale trial is warranted.